Acute pancreatitis: An initial presentation of systemic lupus erythematosus - Gholamhossein ALISHIRI,; Nooshin BAYAT,; Hadi KHAJEHPOOR,; Mehrdad NOORANIPOUR,; Mohammad Ebrahim GHAMARCHEHREH, (Turkish Journal of Gastroenterology, 2019)
-